Predicting Flow-Induced Acoustics at Near-Stall Conditions in an Automotive Turbocharger Compressor A Numerical Approach - Navarro García, Roberto (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This thesis offers new insights into the fluid flow behavior of automotive centrifugal compressors operating under near-stall conditions. Firstly it discusses the validation of three-dimensional computational fluid dynamics (CFD) unsteady simulations against acoustic experimental measurements using an original procedure based on plane wave pressure decomposition. It then examines the configuration of the CFD cases, highlighting the key parameters needed for a successful calculation. Moreover, it describes both the compressor mean and unsteady flow field from best-efficiency to near-surge operating points. Lastly, it provides readers with explanations of the various phenomena that arise when the mass flow rate is reduced and the compressor is driven to poor and noisy performance. Written for students, researchers and professionals who want to improve their understanding of the complex fluid flow behavior in centrifugal compressors, the thesis offers valuable practical insights into reducing the acoustic emissions of turbochargers.